DRONE-ASSISTED ROOF INSPECTIONS: ADVANCING STRUCTURAL MONITORING AND MAINTENANCE OF FLAT ROOFS IN URBAN ENVIRONMENTS - Григорович, Микита (SWorldJournal, 2025)
Flat roofs comprise a modest share of Ukraine’s overall housing sector, yet they dominate many multi-apartment developments due to Soviet-era construction approaches favoring flat concrete structures. Despite early concerns regarding snow accumulation an